In vitro plant regeneration from immature embryo axis and cotyledons of common bean (Phaseolus vulgaris L.) - Eissa Ahmed, H. (International Journal of Horticultural Science, 2005)
Phaseolus vulgaris L. is the most important economic species within the genus Phaseolus. It is grown in all parts of the world. Genetic improvement by conventional breeding has met considerable success, although production of hybrids between species within the genus has been limited due to sexual incompatibility. Recent advances in tissue culture have offered the opportunity to produce cultivars, which could not be obtained by conventional breeding methods. The use of tissue culture and genetic engineering is viewed as a logical approach to improve bean production. Gene transfer techniques will have a great impact on legumes. Although the concept of cell totipotency is widely proved, in vitro morphogenesis has not yet been achieved for a large number of cultivated beans. Regeneration protocols are strongly influenced by the genotype. In tissue and cell culture of beans, the factors controlling shoot morphogenesis and somatic embryogenesis are still unknown. The reported data suggest a possible way for future research.